Analysis of The Process of Implementing Character Education in Overcoming The Moral Crisis of Class X Students at SMA Brigjend Katamso 1 Medan - Nababan*, Surya Aymanda; Darma, Aditya; Kaban, Benny Junior; Laia, Forman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to educate character in overcoming the moral crisis of grade X students at SMA Brigjend Katamso 1 Medan, considering that many students have a crisis of good character and morals. The method used in this study is to cultivate moral and religious values to students. So that the younger generation is able to understand their shortcomings and strengths as a source of grace from God that must be grateful. With this method can create an attitude of confidence, decrease violations of social rules that apply in society, the younger generation is able to show logical and creative thinking. In today's world of education, character education in overcoming students' moral crisis has begun to decrease. It can be proven by the number of students who lack respect, respect, and are not polite to people around them, especially in the school environment. This is due to the underestimation and non-compliance with applicable regulations in the school environment and also caused by the influence of the surrounding environment such as digital lifestyle, both from home, and also from friends. The digital era not only has a positive impact, but also a negative impact. For this reason, those who must play an active role in preventing a moral crisis of students like this are parents, especially and also teachers who teach in their schools. So that by preventing this student moral crisis, it can slowly realize character education in overcoming the moral crisis of students in class X at SMA Brigjend Katamso 1 Medan.